Pengaruh Person-Job Fit dan Person-Organization Fit Terhadap Kinerja Karyawan PT. Sumatraco Langgeng Makmur - Sayuga, Hadad Dinanjar; Ambarwati, Arie; Fatmawati, Rini (Jurnal Ilmiah Administrasi Bisnis dan Inovasi, 2023)
This research is motivated by facts or phenomena that are happening at this time, namely the fit between personality and work (Person-Job Fit) and the fit between personality and company environment/culture (Person-Organization Fit) which still influence employee performance at PT. Sumatraco Langgeng Prosperous. This study uses a quantitative approach and the type of research used is explanation/relationship. The sample used in this study amounted to 225 respondents. The results of this study using multiple regression methods can be concluded that partially the person-job fit variable has a significant influence on employee performance with a significance value of 0.000 <0.05 and also tcount (5.577) > ttable (1.972). Meanwhile, the person-organization fit variable also has a significant influence on employee performance with a significance value of 0.000 <0.05 and tcount (3.941) > ttable (1.972). Simultaneously the variables person-job fit and person-organization fit have a significant effect on employee performance with a significance value of 0.000 <0.05 and also the value of Fcount (42.088) > Ftable (4.7)